Development of Food Chain Magic Box Media Based on Problem Based Learning to Improve the Learning Outcomes of Elementary School Grade V Students - Maharani Novtia Putri Amanda; Desi Wulandari (Postgraduate, University of Mataram, 2025)
This study uses the type of Research and Development (R&D) development research with the Borg and Gall development model which aims to develop, test the feasibility and effectiveness of food chain magic box media based on problem-based learning. The population in the study consisted of 6 subjects for small-scale tests from class V of SDN Ngaliyan 03 and 26 subjects for large-scale tests from class V of SDN Ngaliyan 05. The data collection techniques used are test and non-test techniques. The results of the product validation assessment obtained an average percentage of 92.5% from media validators and an average percentage of 90% from material validators with both categories being very feasible. The results of the pretest and posttest of students in the small-scale test have increased with an average difference of 43.4 and N-Gain of 0.7801 with a high category. In large-scale tests, there was also an increase in pretest results, judging from the posttest results obtained with an average difference of 47 and an N-Gain of 0.7801 with a high category. This proves that the use of food chain magic box media based on problem-based learning in class V social studies learning is effective in improving the learning outcomes of social studies for grade V students of SDN Ngaliyan 05.